EFFECT OF ADMINISTRATION OF hCG BEFORE THE ONSET OF OESTRUS FOLLOWING PGF2α TREATMENT ON CONCEPTION RATE IN REPEAT BREEDER COWS - Selvaraju, M; Veerapandian, C; Kathiresan, D; Kulasekar, K; Chandrahasan, C (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Regulating oestrus using oestrus synchronizing agents may help to increase the conception rate in repeat breeder cows. A total of 48 repeat breeder cows were divided into 3 groups viz., group I, II and III. Cows in group I and II were treated with 0.98 mg of Tiaprost (PGF2α) on day 10 following natural oestrus (day 0). Group III cows, served as control without any treatment. AI was done at 72 (first AI) and 96 (second AI) hours following PGF2α therapy in group I and II. Group III cows were artificially inseminated twice at 24 hours interval during natural oestrus. Group II cows were injected with 1500 IU hCG at 24 hours prior to first AI. There was 100 per cent oestrus response in PGF2α treated cows in group I and II. The first service conception rate obtained was 43.75, 43.75 and 18.75 per cent, in group I, II and III, respectively.